ANALISIS SISTEM PENGENDALIAN INTERNAL ATAS PENERIMAAN DAN PENGELUARAN KAS PADA MASJID JAMI’ AN-NUR JAKARTA SELATAN - Prameswari, Rahma Dyah; Nasution, Hafifah; Nindito, Marsellisa (LPPM Universitas Bina Bangsa, 2025)
This research aims to analyze the internal control system for cash receipts and disbursements currently implemented at the Jami' An-Nur Mosque, South Jakarta, when viewed from the Internal Control Framework of the Committee of Sponsoring Organizations (COSO). This research is a type of qualitative research. The data collection techniques used were interviews and documentation. The research results show that the internal control system for cash receipts and disbursements implemented at the Jami' An-Nur Mosque does not fully meet the criteria of the COSO Internal Control Framework. Of the five components in the COSO Internal Control Framework, component information and communication have been implemented according to the criteria. However, the components of the control environment, risk assessment, control activities and monitoring have not been implemented according to the criteria.